Modeling conformational transitions in kinases by molecular dynamics simulations: achievements, difficulties, and open challenges - D'Abramo, Marco; Besker, Neva; Chillemi, Giovanni; Grottesi, Alessandro (Frontiers in Genetics, 2014)
Protein kinases work because their flexibility allows to continuously switch from inactive to active form. Despite the large number of structures experimentally determined in such states, the mechanism of their conformational transitions as well as the transition pathways are not easily to capture. In this regard, computational methods can help to shed light on such an issue. However, due to the intrinsic sampling limitations, much efforts have been done to model in a realistic way the conformational changes occurring in protein kinases. In this review we will address the principal biological achievements and structural aspects in studying kinases conformational transitions and will focus on the main challenges related to computational approaches such as molecular modeling and MD simulations.